Combind Effect of Machining Parameters With Nose Radius of the Custting Tool on Surface Roughness of 304- Austenitic Stainless Steel Alloy Produced by Cnc-Turning Machin - Senussi, Galal H (Review of Industrial Engineering Letters, 2014)
It is well known that machining parameters have strong effect on the properties of surface roughness. Many investigations have done on this area. This work studies of combining effect of turning process parameters (cutting speed, feed rate, and depth of cut) with on surface roughness. Where, nose radius of the tool and machining parameters have taken as input variables and the surface roughness (Ra) as response or output. Three experiments were conducted; they were used to investigate the surface roughness resulted by tool corner radiuses of the values: 0.4mm, 0.8mm, and 1.2mm Response surface methodology (R.S.M) is applied as a tool to show the cause and effect of output (response) and input control and relationship between them as a two or three dimensional hyper surface. A three factor with five level central composite rotatable factors design was used. The results showed that R.S.M is a strong tool and capability tool to predict the effect of machining parameters on surface roughness. Results improved that the five level factorial designs can be employed for developing statistical models to predict surface roughness by controllable machining parameters. Results showed that the combined effect of cutting speed at its higher level, feed rate and depth of cut at their lower values, and large nose radius can result in better surface roughness.